Intrusion Response System based on Time Management Concept with the Critical IP Address as a Parameter - Ariani, Muhammad Salman (International Journal of Advanced Science and Technology, 2020)
The intrusion response system is a component to improve the performance of network security intrusion detection systems (IDS) for choosing the right and optimal response options. An administrator can perform response actions based on the severity of the IDS which is determined by the vulnerability score on CVE based on the CVSS metric base. However, with a large number of intrusions on the internet, an appropriate response is needed by paying attention to the target intrusion to prioritize which intrusion must be resolved. So, we have to determine response options for the most critical assets. The parameters for it are the IP address because the IP address is one of the cores of the internet, which can show the identity of the institution owner the IP.